Acute syndrome of apoptotic pan-epidermolysis successfully treated with intravenous immunoglobulin and steroid combination - Şentürk, Nilgun; Losol, Enkhjargal; Kelleci, Yusuf; Özdemir, Hilal; Bayçelebi, Deniz; Yıldız, Levent (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Acute syndrome of apoptotic pan-epidermolysis (ASAP) is a recently described syndrome that is characterized by acute and massive cleavage of the epidermis resulting from hyperacute apoptotic epidermal basal cell injury [1]. This phenomenon is classically seen in drug-induced toxic epidermal necrolysis (TEN), but occasionally occurs in other conditions called ‘TEN-like’ diseases (e.g., lupus erythematosus (LE), acute graft versus host disease (GVHD) and pseudoporphyria) [2, 3].